Ananlisis Bibliometrik Mengenai Pemahaman Nilai-nilai Multiikultural dengan Bimbingan Kelompok Teknik Karyawisata - Berlian Hati, Angela Amanda; Khusumadewi, Ari; Purwoko, Budi; Winingsih, Evi (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
The role of multicultural values for society, especially the younger generation, is very important, namely so that people can live together by having complementary attitudes and feelings so as to create a peaceful and prosperous life. This research uses bibliometric analysis of published works that discuss related research on multicultural values. The objectives of the research are: 1) Presenting an in-depth bibliometric analysis as a basis for understanding the latest developments and trends in multicultural values, 2) Knowing the development of the number of published articles on the topic of multicultural values and 3) Analyzing the results of visualization of trends in the discussion of multicultural values. The research data was sourced from Google Scholar with a publication period of 5 years (2019-2024) and processed using Publish or Perish and VOSviewer software. The results of the analysis found that the development of published works with the trend of “multicultural values” is significantly increasing and increasingly varied in the discussion of related research. It is hoped that through the research findings there are many parties who are helped and make research as material in conducting further research on related discussions.